Costs Associated with Ambulatory Care Sensitive Conditions Across Hospital‐based Settings. (29th January 2015) - Galarraga, Jessica E.; Mutter, Ryan; Pines, Jesse M.; Schneider, Sandra
Abstract Objectives Ambulatory care sensitive conditions (ACSCs) are acute care diagnoses that could potentially be prevented through improved primary care. This study investigated how payments and charges for these ACSC visits differ by three hospital‐based settings (outpatient, emergency department [ED], and inpatient) and examined differences in payments and charges by their physician and facility components. Methods This was a secondary analysis of data (2005 through 2010) from the Medical Expenditure Panel Survey. Multiple linear regression models were used to assess differences in the mean‐adjusted payments and charges for ACSC visits by clinical setting and further divided payments and charges into physician and facility components. Results Of all ACSC visits from 2005 through 2010, 41% were outpatient visits, 36% were ED visits, and 23% were hospital admissions. After adjusting for patient demographics and comorbid conditions, charges for an inpatient ACSC visit were four times higher (11, 414 vs. 2, 563) and payments were five times higher (4, 325 vs. 859) when compared to an ED visit. By comparison, charges for an ACSC ED visit were two times higher (2, 563 vs. 1, 084) and payments 2.5 times higher (859 vs. 341) relative to an ACSC visit managed in an outpatient hospital‐based clinic. Across all clinical settings, hospital facility fees account for 77% to 94% of the charge differences and 81% to 93% of the payment differences. Conclusions For hospital‐based ACSC visits, inpatient hospitalizations are by far the most expensive. Finding ways to expand outpatient resources and improve the health management of the chronically ill may avoid conditions that lead to more expensive hospital‐based encounters. Across all hospital‐based settings, facility fees are the major contributor of expense.